Magnitude and Associated Factors of Awareness with Recall under General Anesthesia in Amhara Regional State Referral Hospitals, 2018 - Tadese Tamire; Habtamu Demelash; Tikuneh Yetneberk; Simegnew Kibret (Anesthesiology Research and Practice)
Introduction. Awareness with recall of intraoperative events is an infrequent but potentially devastating complication of general anesthesia, with a reported incidence of 0.1-0.2% in low-risk patients. Higher incidence is expected in resource-limited operation room setups and in high-risk patients. Awareness can result in significant distress to patients and long-term psychological consequences, including symptoms associated with posttraumatic stress disorder, anxiety, night mares, night terror, dissatisfaction with surgical service, and sometimes even suicide. Objective. To assess the magnitude and associated factors of awareness with recall under general anesthesia in Amhara regional state referral hospitals. Method. An institution-based cross-sectional study was conducted on 1065 patients who underwent surgery under general anesthesia from January 1 to June 30, 2018. The study participants were selected by systematic random sampling from 4 referral hospitals. The modified Brice questionnaire was used to detect awareness under general anesthesia. Interviewer-administered structured questionnaire and chart review were employed. Data with complete information were entered in to SPSS version 20 computer software. Descriptive statics and bivariate and multivariable analysis were computed. A P-value less than 0.2 was used to select candidate variables for multivariable logistic regression. A P-value less than 0.05 was used to declare statistical significance. Result. 1065 patients were included in the study which makes the response rate of 90.7%. The magnitude of awareness with recall under general anesthesia was found to be 8.2% of which 4.9%, 2.6%, and 0.7% of patients reported hearing voice, pain, and sensation of breathing tube, respectively. Lack of premedication was the only significantly associated factor for awareness with recall under general anesthesia (AOR = 3.014, 95% CI (1.201 to 7.565)). Conclusion and Recommendation. Our study showed higher magnitude of awareness with recall under general anesthesia. Lack of premedication was the only associated factor with awareness with recall under general anesthesia. Anesthetists should give emphasis to prevent the possibility of awareness under general anesthesia by providing premedication. Cohort studies should be done including the consequences of awareness with recall under general anesthesia.